The Effect of Transformational Leadership and Workload on Employee Performance: JEL Classification: M12, M54, J24, J81, O15 - Sunastri Sunastri; Mujahid Yunus; Abdul Samad (Newinera Publisher, 2025)
This study aims to analyze and examine the influence of transformational leadership and workload on employee performance at the Airport Authority Office Region V Makassar. Data were collected through questionnaires, with a total of 116 respondents selected using the Slovin formula. The questionnaire was tested for validity and reliability, and classical assumption tests such as normality, multicollinearity, and heteroscedasticity were also conducted. The data analysis method used was multiple linear regression. The results of the study show that: (1) Transformational leadership has a positive and significant effect on employee performance; (2) Workload also has a positive and significant effect on employee performance; and (3) simultaneously, transformational leadership and workload have a positive and significant effect on employee performance at the Airport Authority Office Region V Makassar. The coefficient of determination (R Square) value of 0.319 indicates that 31.9% of the variation in employee performance can be explained by these two variables, while the remaining 68.1% is influenced by other factors not included in this study.